Development Strategy of Agrotourism in Malasari Tourism Village Based on Villagers - Kurniawan, Taufiq; Hariya, Rahadrian Ksatria (Jurnal Sains Sosio Humaniora, 2024)
Malasari Village is located in Nanggung Subdistrict and is the largest village in the area, covering approximately 8,262 hectares. Despite its large area, the population is less than 10,000 people, as a significant portion of the village comprises the protected forest area of Mount Halimun Salak National Park. Owing to its rich natural potential, Malasari Village was designated as a tourism village in 2015. The main attractions of Malasari Tourism Village include the Nirmala tea plantation, one of the oldest tea plantations in West Java. Additionally, the village features several waterfalls such as Curug Piit, Curug Sawer, Curug Macan, Curug Antin, Curug Tujuh, and Curug Kembar. This study employs a qualitative method through in-depth interviews with local community informants. Data analysis is conducted using the SWOT (Strengths, Weaknesses, Opportunities, Threats) method and utilizes the 5A indicators (Amenities, Accesses, Attractions, Activities, Accommodations) as a reference for developing agrotourism strategies in Malasari Tourism Village. Based on the research findings, the following conclusions can be drawn: (1) Amenities: The facilities are inadequate, particularly the limited parking space. (2) Access: The main road leading to the village is in poor and risky condition. (3) Attractions: The village boasts unique attractions, such Nirmala Tea Plantation, Curug Macan, Cikaniki Research Center, and Nirmala Rose Garden. (4) Activities: Activities include tea leaf picking; however, tourism packages related to this activity are not well marketed. (5) Accommodations: The village has sufficient homestays and camping grounds.